2019
DOI: 10.3389/fnins.2018.01058
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic Nervous System Activation and Its Modulation: Role in Atrial Fibrillation

Abstract: The autonomic nervous system (ANS) has a significant influence on the structural integrity and electrical conductivity of the atria. Aberrant activation of the sympathetic nervous system can induce heterogeneous changes with arrhythmogenic potential which can result in atrial tachycardia, atrial tachyarrhythmias and atrial fibrillation (AF). Methods to modulate autonomic activity primarily through reduction of sympathetic outflow reduce the incidence of spontaneous or induced atrial arrhythmias in animal model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 207 publications
(233 reference statements)
1
32
0
1
Order By: Relevance
“…Hypertension is a common cardiovascular risk factor, and hypertensive heart disease can manifest as several cardiac arrhythmias [ 37 , 38 ]. Hypertension can lead to left ventricular hypertrophy and myocardial fibrosis and can trigger arrhythmia by activating the sympathetic nervous system and the renin–angiotensin–aldosterone system [ 39 , 40 ]. Mechanical overload due to high blood pressure may induce an abnormal expression of ion channels and/or junctional complexes [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension is a common cardiovascular risk factor, and hypertensive heart disease can manifest as several cardiac arrhythmias [ 37 , 38 ]. Hypertension can lead to left ventricular hypertrophy and myocardial fibrosis and can trigger arrhythmia by activating the sympathetic nervous system and the renin–angiotensin–aldosterone system [ 39 , 40 ]. Mechanical overload due to high blood pressure may induce an abnormal expression of ion channels and/or junctional complexes [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, it has been reported that AF activates the autonomic nervous system in both animal model and human studies. 7 , 8 Furthermore, a recent study reported that arrhythmogenesis in the RVOT is associated with sympathetic fibers in the animal model. 1 Therefore, the increased sympathetic tone induced by AF would play an important role in the induction of RVOT arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…The imbalanced state of the ANS has been gradually recognized in AF associated with OSA (Carnagarin et al, 2019;Huang et al, 2020). Treatment measures that modulate the ANS, including metoprolol (Li et al, 2015;Sun et al, 2017;Dai et al, 2019) and LLTS (Yu et al, 2017b), could inhibit the inducibility of AF.…”
Section: Slgp Ablation Failed To Reversementioning
confidence: 99%